Propranolol Blocks Cardiac and Neuronal Voltage-Gated Sodium Channels - Wang, Dao W.; Mistry, Akshitkumar M.; Kahlig, Kristopher M.; Kearney, Jennifer A.; Xiang, Jizhou; George, Alfred L. (Frontiers in Pharmacology, 2010)
Propranolol is a widely-used, nonselective ß-adrenergic receptor antagonist with proven efficacy in treating cardiovascular disorders and in the prevention of migraine headaches. At plasma concentrations exceeding those required for ß-adrenergic receptor inhibition, propranolol also exhibits antiarrhythmic (“membrane stabilizing”) effects that are not fully explained by ß-blockade. Previous in vitro studies suggested that propranolol may have local anesthetic effects We directly tested the effects of propranolol on heterologously expressed recombinant human cardiac (NaV1.5) and brain (NaV1.1, NaV1.2, NaV1.3) sodium channels using whole-cell patch-clamp recording. We found that block was not stereospecific as we observed approximately equal IC50 values for tonic and use-dependent block by R-(+) and S-() propranolol (tonic block: R: 21.4 uM vs S: 23.6 uM; use-dependent block: R: 2.7 uM vs S: 2.6 uM). Metoprolol and nadolol did not block NaV1.5 indicating that sodium channel block is not a class effect of ß-blockers. The biophysical effects of R-(+)-propranolol on NaV1.5 and NaV1.1 resembled that of the prototypical local anesthetic lidocaine including the requirement for a critical phenylalanine residue (F1760 in NaV1.5) in the domain 4 S6 segment. Finally, we observed that brain sodium channels exhibited less sensitivity to R-(+)-propranolol than NaV1.5 channels. Our findings establish sodium channels as targets for propranolol and may help explain some beneficial effects of the drug in treating cardiac arrhythmias, and may explain certain adverse central nervous system effects.